Three-dimensional spatial hand patterns of skilled butterfly swimmers - Barthels, K. M.; Adrian, M. J. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
The purpose of the investigation was to identify the three-dimensional underwater motion of the hand with respect to still water during the performance of the butterfly stroke, with and without the kick, and to relate this hand motion to the horizontal motion of the swimmer's body.